Model Participatory Experiential Learning untuk Peningkatan Literasi Investasi Digital Aparatur Pemerintah Daerah - Winarsih, Wiwin; Ekawarti, Yuni; Veronica, Aries; Alfiana, Yeni; Widyastuti, Sari Mustika; Yanti, Dwi (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This community service program aimed to enhance digital investment literacy among employees of the South Sumatra Provincial Communication and Information Office (Diskominfo), particularly millennials and Gen Z, through the application of the Participatory Experiential Learning (PEL) Approach. Methodology/approach: Findings indicate an overall improvement in digital investment literacy. Significant progress was observed in differentiating between fixed-income and growth-oriented instruments mean score 3.95 to 4.17 and in evaluating portfolio performance from score 3.73 to 4.17. Moderate improvements were found in investment horizon and risk awareness, whereas slight decreases occurred in linking welfare with investment capacity and aligning risk profiles with financial goals. Results/findings: The findings indicated a significant improvement in participants’ knowledge and skills. The average post-test scores were notably higher than pre-test scores, demonstrating enhanced understanding of financial management and confidence in selecting appropriate digital investment instruments such as mutual funds, stocks, and digital-based financial products. Conclusions: The PEL approach effectively improved digital investment literacy among young government employees by combining experiential and participatory learning. Limitations: The study was limited to 33 participants from a single institution, with effectiveness measured only through pre- and post-tests, and without longitudinal evaluation. Contribution: This program contributes to strengthening digital financial literacy capacity among government employees and provides an experiential learning-based model that may be replicated in similar institutions and communities.